RETRACTED: Comparison of turbulence models for the axisymmetrical separated boundary layer problem - Madaliev Murodil; Usmonov Mavlonbek; Soliyev Oybek; Otajonov Jamshidbek; Kadirov Khasanboy; Otakhanova Zamira; Mavlonova Dilnoza (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001